LPA2 protein is involved in photosystem II assembly in Chlamydomonas reinhardtii. (31st July 2021) - Cecchin, Michela; Jeong, Jooyeon; Son, Woojae; Kim, Minjae; Park, Seunghye; Zuliani, Luca; Cazzaniga, Stefano; Pompa, Andrea; Young Kang, Chan; Bae, Sangsu; Ballottari, Matteo; Jin, EonSeon
Summary: Photosynthetic eukaryotes require the proper assembly of photosystem II (PSII) in order to strip electrons from water and fuel carbon fixation reactions. In Arabidopsis thaliana, one of the PSII subunits (CP43/PsbC) was suggested to be assembled into the PSII complex via its interaction with an auxiliary protein called Low PSII Accumulation 2 (LPA2). However, the original articles describing the role of LPA2 in PSII assembly have been retracted. To investigate the function of LPA2 in the model organism for green algae, Chlamydomonas reinhardtii, we generated knockout lpa2 mutants by using the CRISPR‐Cas9 target‐specific genome editing system. Biochemical analyses revealed the thylakoidal localization of LPA2 protein in the wild type (WT), whereas lpa2 mutants were characterized by a drastic reduction in the levels of D1, D2, CP47 and CP43 proteins. Consequently, reduced PSII supercomplex accumulation, chlorophyll content per cell, PSII quantum yield and photosynthetic oxygen evolution were measured in the lpa2 mutants, leading to the almost complete impairment of photoautotrophic growth. Pulse‐chase experiments demonstrated that the absence of LPA2 protein caused reduced PSII assembly and reduced PSII turnover. Taken together, our data indicate that, in C. reinhardtii, LPA2 is required for PSII assembly and proper function. Significance Statement: LPA2 is a nuclear‐encoded protein that is suggested to be involved in PSII assembly in vascular plants. Here, using CRISPSRS/CAS9 mutagenesis, we identified and investigated an LPA2 homolog in Chlamydomonas reinhardtii . lpa2 mutants were characterized by a strong reduction in the accumulation of photosystem II core subunits, reduced photosystem II activity, increased photosensitivity and impairment in photoautotrophic growth, revealing the critical role of LPA2 in the assembly of photosystem II supercomplexes in green algae.